1999
DOI: 10.1002/(sici)1099-1573(199908/09)13:5<419::aid-ptr470>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daniellia oliveri stem bark and leaf extracts on rat skeletal muscle

Abstract: The stem bark and leaves of Daniellia oliveri were screened phytochemically and the effects of their respective methanol extracts on the skeletal muscle of rats were investigated using the isolated phrenic nerve hemidiaphragm muscle preparation. Both were found to contain tannins, cardiac and saponin glycosides. In addition, the bark, but not leaves, contained cyanogenetic glycosides. The methanol extracts were found to possess neuromuscular blocking properties. The leaf extract appeared to act primarily by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several research investigating various pharmacological activities have been done on the plant. The stem bark methanol extract has been shown to have neuromuscular blocking activity [8]. The oleoresin has antioxidant anticytotoxic activities [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several research investigating various pharmacological activities have been done on the plant. The stem bark methanol extract has been shown to have neuromuscular blocking activity [8]. The oleoresin has antioxidant anticytotoxic activities [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Scientific studies have revealed that the roots, stems, and leaves demonstrated a considerable antimicrobial (Jimoh and Oladiji, 2005), anti-inflammatory (Oyegade et al, 1999;Muanda et al, 2011), cytotoxic (Topcu et al, 1993;, antihyperglycaemic (Iwueke and Nwodo, 2008), antioxidant (Ahmadu et al, 2004), anti-diarrheal (Ahmadu et al, 2007), immunostimulatory (Lamy et al, 2010), hepatoprotective (Olatunji, 2000;Alagbe et al, 2017) and miracicidal activities (Arnao et al, 1998;. The plant parts contain various phytochemicals (tannins, flavonoids, saponins, phenols, alakloids, terpenoids, glycosides), minerals, amino acids, and vitamins and they can be traditionally used for the treatment of malaria, typhoid, skin diseases, gastro intestinal infections, urinary infections and toothache Onwukaeme et al, 1999;Musa et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac glycosides present in the methanol extract of the bark showed non-competitive antagonism on muscarinic receptors on isolated rat bladder smooth muscle (Onwukaeme et al, 1999a). Methanol extracts of the leaves and stem bark were showed to possess neuromuscular blocking properties on rat skeletal muscle (Onwukaeme et al, 1999b). The smoke of the bark of D.…”
Section: Daniellia Oliverimentioning
confidence: 96%